DNA Helicase–Polymerase Coupling in Bacteriophage DNA Replication - Lo, Chen-Yu; Gao, Yang (Viruses, 2021)
Bacteriophages have long been model systems to study the molecular mechanisms of DNA replication. During DNA replication, a DNA helicase and a DNA polymerase cooperatively unwind the parental DNA. By surveying recent data from three bacteriophage replication systems, we summarized the mechanistic basis of DNA replication by helicases and polymerases. Kinetic data have suggested that a polymerase or a helicase alone is a passive motor that is sensitive to the base-pairing energy of the DNA. When coupled together, the helicase–polymerase complex is able to unwind DNA actively. In bacteriophage T7, helicase and polymerase reside right at the replication fork where the parental DNA is separated into two daughter strands. The two motors pull the two daughter strands to opposite directions, while the polymerase provides a separation pin to split the fork. Although independently evolved and containing different replisome components, bacteriophage T4 replisome shares mechanistic features of Hel–Pol coupling that are similar to T7. Interestingly, in bacteriophages with a limited size of genome like Φ29, DNA polymerase itself can form a tunnel-like structure, which encircles the DNA template strand and facilitates strand displacement synthesis in the absence of a helicase. Studies on bacteriophage replication provide implications for the more complicated replication systems in bacteria, archaeal, and eukaryotic systems, as well as the RNA genome replication in RNA viruses.